Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Pegawai (Studi Kasus Pada Pegawai Desa di Kecamatan Plered) - Ismail Ludin; Saepul Mukti; Ibnu Saepul Rohman (Fakultas Ekonomi, 2023)
This research aims to find out how the influence of compensation and work discipline on employee performance in villages in Plered District. The examination technique utilized is quantitative with an all out example of 117 individuals. The information sources utilized in this study was essential acquired from survey. The gathered information was tried through information test and hipotheses test through twofold straight relapse with SPSS rendition 26. The outcomes showed both somewhat and all the while that pay and work discipline affected the exhibition of town representatives in Plered Area where the remuneration variable was the most predominant component. In total, the effect of the two independent variables is 54.7%.